A dictionary of mechanical engineeringg - Atkins, Anthony G. 1939-; Escudier, Marcel (Oxford paperback reference, 2013)
This new dictionary covers all aspects of mechanical engineering, including thermodynamics, heat transfer, combustion, stress analysis, design, manufacturing, materials mechanics, dynamics, vibrations, and control. It provides authoritative guidance for students, practising engineers, and others needing definitions of mechanical engineering terms.